PENGARUH LATIHAN JUMP TO BOX DAN SQUAT JUMP DENGAN METODE INTERVAL PENDEK TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI DAN KEMAMPUAN SMASH ATLET BOLA VOLI PUTRA DIAMOND VC TAHUN 2024 - Tua Sihotang , Parulian; Amansyah (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to determine the effect of jump to box and squat jump training using the short interval method on increasing the explosive power of leg muscles and smash ability of Diamond VC volleyball club athletes in 2024. The research location was carried out at the Diamond VC Club training ground, Jl. Alfaka V Tanjung Mulia Hilir, Medan, North Sumatra. The population in this study was 23 athletes with a sample of 10 athletes selected using Purposive Sampling technique. This research uses quantitative methods with data collection techniques in this research carried out by pretest and posttest, while data analysis techniques use descriptive statistics, prerequisite tests and hypothesis testing. The results of this study show that there is a significant influence between Jump To Box and Squat Jump training using the short interval method on increasing the explosive power of leg muscles and the smash ability of Diamond VC Volleyball Club athletes. This can be seen from the results of the research which shows that the explosive power of leg muscles increases and the athlete's smash ability with jump to box and squat jump training using the short interval method with the pretest and posttest r calculated value of leg muscle explosive power using the vertical jump measurement test is Tcount 8.387 > Ttable 1.833 while the pretest and posttest score for the smash test is Tcount. 5.277 > Ttable 1.833 at a significance level of 5% and degrees of freedom (db) = n-2 (10-2) = 8. Because Tcount > Ttable it can be concluded that there is a significant influence between Jump To Box and Squat Jump training with the interval method short on increasing the explosive power of the leg muscles of Diamond VC Volleyball Club athletes in 2024